Renewable Energy Transition: Evidence from Spillover Effects in Exchange-Traded Funds - Lisin, Anton; Senjyu, Tomonobu (International Journal of Energy Economics and Policy, 2021)
The article examines the spillover effect of the transition to renewable energy on different financial markets: specifically, the stock market. The research paper analyzes the prices and dynamics of oil-related assets and renewable funds, as well as reviews literature on the topic in order to evaluate the most important factors of development in these industries. The article utilizes methods of correlation analysis, analysis of variance, regression analysis and standards of deviation and error with the intention to test null hypotheses from previous research. The study uses empirical data spanning the majority of the last decade, in which a decline in the oil market can be observed. This is juxtaposed by the rapid and intense development of renewable energy – solar energy in particular. As concluded in the article, there is a strong spillover effect of this growth onto other markets, emphasizing the investments flowing into renewable energy. Moreover, the ambitious prospects of renewable energy development and it being a strong competitor to fossil fuels and, specifically, oil is drawn as a result of the conducted research. Keywords: Spillover effect, solar energy, oil energy, transition, energy investments. JEL Classifications: C12, C52, E23, Q41 DOI: https://doi.org/10.32479/ijeep.10899